Proceedings of the 2019 CHI Conference on Human Factors in Computing Systems 2019
DOI: 10.1145/3290605.3300754
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Web Browser Reader Views on Reading Speed and User Experience

Abstract: As reading increasingly shifts from paper to online media, many web browsers now provide a "Reader View," which modifies web page layout and design for better readability. However, research has yet to establish whether Reader Views are effective in improving readability and how they might change the user experience. We characterize how Mozilla Firefox's Reader View significantly reduces the visual complexity of websites by excluding menus, images, and content. We then conducted an online study with 391 partici… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(14 citation statements)
references
References 39 publications
0
13
1
Order By: Relevance
“…Furthermore, the survey questions that returned similar results between conditions also raise various points for discussion. When prior work examined browser reader views where ads were removed (as well as other visual elements such as images), users perceived the visual appeal of the webpage to significantly increase [41]. Yet, the present study found that participants rated the system with and without ads as having the same levels of aesthetic appeal.…”
Section: Discussioncontrasting
confidence: 66%
See 1 more Smart Citation
“…Furthermore, the survey questions that returned similar results between conditions also raise various points for discussion. When prior work examined browser reader views where ads were removed (as well as other visual elements such as images), users perceived the visual appeal of the webpage to significantly increase [41]. Yet, the present study found that participants rated the system with and without ads as having the same levels of aesthetic appeal.…”
Section: Discussioncontrasting
confidence: 66%
“…Secondly, in different research investigating aggregated search -where different types of media such as images or news are blended into the same search engine result page (SERP) -users rated the blended interface as significantly less usable [65]. Similarly, when web browser reader views have been implemented -which strips back webpage complexity through excluding items such as menus and images -users perceived the visual appeal of the page to significantly increase and were able to read pages 5% faster [41]. Although these three examples cover a range of visible elements during online search, they all concluded similar results that increased elements on a webpage are associated with more negative perceptions.…”
Section: Increasing Visible Webpage Elementsmentioning
confidence: 99%
“…Reading on a device, such as a tablet or phone, has predominantly taken the place of traditional formats (Li et al, 2019). Such devices allow access to implicit user feedback by measuring how a user interacts with the text they read.…”
Section: Implicit Feedback Techniquesmentioning
confidence: 99%
“…We present the system features and design choices in a fictional usage scenario where Emma, an HCI researcher, uses the visualizer to explore a multiverse on data collected in her experiment. We construct the multiverse based on how the authors of a published research article [28] might analyze their data, but the name "Emma" and her workflow are fictional.…”
Section: The Boba Visualizermentioning
confidence: 99%